2014
DOI: 10.1172/jci74237
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet–induced microRNAs and mTOR underlie β cell dysfunction in offspring

Abstract: data indicate that mTORC1 signaling is essential for attenuating β cell dysfunction induced by maternal low-protein diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 63 publications
4
106
0
Order By: Relevance
“…Degradation of Drosha results in reduced miRNA processing and global downregulation of steady-state miRNA levels. These new findings emphasize the impact that nutrients and the cellular environment have on miRNA biogenesis and compliment results observed in mouse studies, where maternal diet was shown to alter a subset of miRNAs in the offspring through mTORC1 (Alejandro et al, 2014). …”
supporting
confidence: 82%
“…Degradation of Drosha results in reduced miRNA processing and global downregulation of steady-state miRNA levels. These new findings emphasize the impact that nutrients and the cellular environment have on miRNA biogenesis and compliment results observed in mouse studies, where maternal diet was shown to alter a subset of miRNAs in the offspring through mTORC1 (Alejandro et al, 2014). …”
supporting
confidence: 82%
“…found that maternal chromium restriction increases plasma glucose (from 9 months), and the area under the curve of glucose during oral glucose tolerance test (from 15 months) in the offspring [16]. The offspring of dams fed a low-protein diet have impaired glucose tolerance at weaning [29] and adulthood [30]. At 12 months of age, offspring from vitamin B 12 -restricted dams have higher blood glucose and impaired glucose tolerance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Protein restriction during pregnancy caused a β-cell secretory defect in adult offspring by increase in the expression of non-coding RNA miR199a-3p and miR-342. Interestingly, these miRNAs were also shown to reduce mTOR levels in isolated β-cells from mice exposed to protein restriction during fetal life 77 . In terms of developmental programming by high fat diet, paternal high fat diet exposure prior to mating induces islet expression of Il13ra2, a protein related to the Jak-Stat signaling pathway, and this change was accompanied by changes in methylation in the transcription start site 79 .…”
Section: Environmental Factors Regulating β-Cell Development and Neonmentioning
confidence: 99%
“…In addition, Hnf4α P2 promoter is epigenetically silenced in islets of the offspring of dams exposed to low protein during gestation 76 . The importance of miR species in developmental programming of β-cell has been recently established 77,78 . Protein restriction during pregnancy caused a β-cell secretory defect in adult offspring by increase in the expression of non-coding RNA miR199a-3p and miR-342.…”
Section: Environmental Factors Regulating β-Cell Development and Neonmentioning
confidence: 99%